Denmark’s innovation system and lessons for Vietnam - Le Thi Thu Huong; Duong Thuy Linh; Nguyen Khanh Chi (Journal SCIENCE AND TECHNOLOGY POLICIES AND MANAGEMENT, 2024)
The innovation system in Denmark is considered a model of a well-structured and well-coordinated framework, effectively combining the long-term vision of the government, academic research, and specialized knowledge in the industry. The strength of Denmark’s innovation system lies not only in financial investment but also in the strategic public-private partnerships, which have become a prominent feature of Denmark’s policies. This collaborative approach is crucial for efficiently transferring research-based knowledge into social applications and commercial joint ventures. This article synthesizes some key components of Denmark’s innovation system and highlights some lessons learned that Vietnam can consider to integrate and promote the development of an innovation system alongside the economic development of the country. Code: 23120901